ANALISIS SISTEM JARINGAN TRANSPORTASI DAN MODEL GRAVITASI DI KOTA AMBON - Surakanti Wardono . Wardono; Paulus A. P; Charles R. Ngangi (Sam Ratulangi University, 2015)
This study aimed to analyze the maximum capacity of roads in overcoming bottlenecks using the Maximum Network Flow Model and analyze the interaction of the distribution of the movement with the city located around the city of Ambon by using Gravity Model. Data obtained using the method of documentation. Obtained results, the maximum number of cars that can pass through the road network in 1 hour is 68 units. Line 1 is the terminal Mahardika to Kudamati has exceeded the capacity for the first hour there are 104 units of the car were gone and behind 102 cars. While the other track is still low, so that the growth and development of land transportation is strongly recommended. Results of the analysis of the gravitational interaction with the transport of the most powerful city of Ambon is Karang Panjang Town with great interaction and 6781.96088 weakest interaction is with great interaction Leahari City 5.27899.